THE SACRED SIGNIFICANCE OF LOCAL WISDOM IN THE BASAPA RITUAL OF MINANGKABAU - Johan Septian Putra; Karali, Nurcan; Syafiq, Amirul (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
The extraordinary enthusiasm of the people attending the Basapa tradition event was generally reasonable because they respected those who had contributed to spreading Islam in Minangkabau and again there were several sacred things attached to Sheikh Burhanuddin so that it became an attraction for pilgrims to attend the rituals carried out every year in the month of Safar. Basapa is a ritual in the form of a simultaneous pilgrimage at the tomb of Sheikh Burhanuddin in Ulakan. Although the cleric figure of Sheikh Burhanuddin of the Tariqa Syattariah congregation, at the Basapa event, those who attended were not only followers of the Syattariah congregation but also the Muslim community in general. The formulation of the problem, namely: What is the background of the development and procession of the Basapa ritual in Ulakan and why the Basapa ritual became sacred in Ulakan, so that it was attended by many people in general from various parts outside the province of West Sumatra. This type of research is included in qualitative descriptive research, as for the systematic series of this research, namely: data sources, data collection techniques and data processing and analysis techniques. The result of the research is that mass pilgrimages occur at the Basapa Ritual which is considered sacred to its followers. The resultant attractive-consolidative Basapa ritual provides reconciliation from various socio-cultural aspects, especially giving the value of cultural inclusiveness to Minangkabau Islam and the sacredness of local wisdom or local wisdom from the Basapa tradition initially based on a religious dimension, but in its improvement, it became a local convention which in the end became a single ethnic identity.